2007
DOI: 10.1111/j.1460-9568.2007.05859.x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration‐enhancing effects of EphA4 blocking peptide following corticospinal tract injury in adult rat spinal cord

Abstract: Spinal cord injury often leads to permanent incapacity because long axons cannot regenerate in the CNS. Eph receptors inhibit axon extension through an effect on the actin cytoskeleton. We have previously reported that after injury EphA4 appears at high levels in stumps of corticospinal axons, while a cognate ligand, ephrinB2, is upregulated at the lesion site so as to confine the injured axons. In this study we have infused lesioned spinal cords with a peptide antagonist of EphA4. In treated animals the retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 44 publications
2
84
0
2
Order By: Relevance
“…EphA4 has been shown previously to play an important role after spinal cord injury. EphA4 knock-out animals show enhanced axon regeneration and less glial scarring after spinal cord injury (Goldshmit et al, 2004), and EphA4-blocking peptides have been shown to enhance spinal axon regeneration (Fabes et al, 2007). Based on this, we hypothesized that EphAs, such as EphA4, on Schwann cells may mediate the inhibitory effect of ephrinAs.…”
Section: Discussionmentioning
confidence: 99%
“…EphA4 has been shown previously to play an important role after spinal cord injury. EphA4 knock-out animals show enhanced axon regeneration and less glial scarring after spinal cord injury (Goldshmit et al, 2004), and EphA4-blocking peptides have been shown to enhance spinal axon regeneration (Fabes et al, 2007). Based on this, we hypothesized that EphAs, such as EphA4, on Schwann cells may mediate the inhibitory effect of ephrinAs.…”
Section: Discussionmentioning
confidence: 99%
“…In spinal cord injured rats, EphA4 protein accumulates in severed CSTaxons, suggesting that they are responsive to ephrin ligands present in myelin (ephrinB3) and scar tissue (ephrinB2) (Fabes et al 2006). It was found that blocking of EphA4 with an infused peptide agonist enhances sprouting of CSTaxons rostral to the injury site but fails to promote axonal regeneration across the lesion into the distal portion of the spinal cord (Fabes et al 2007). Although a regeneration phenotype was reported for spinal cord injured EphA4 null mice through a spinal cord hemisection lesion site (Goldshmit et al 2004), lesion completeness could not be determined with confidence in this report.…”
Section: Ephrinsmentioning
confidence: 99%
“…Behavioral testing in treated rats demonstrated that knocking down EphA4 expression in the injured spinal cord did not improve locomotor recovery but did lead to the development of mechanical allodynia (Cruz-Orengo et al, 2006). A second group that downregulated EphA4-ephrin signaling in the injured spinal cord using a peptide antagonist was able to demonstrate increased locomotor recovery and corticospinal tract sprouting (Fabes et al, 2007). The different finding of these two groups probably reflects differences in how the anti-EphA4 oligonucleotide and blocking peptide work.…”
Section: Sci Treatment Strategies That Block Axon Growth Inhibitorsmentioning
confidence: 99%